Efek profitabilitas Terhadap Nilai Perusahaan dengan Struktur Permodalan Sebagai Variabel Mediasi (Studi Empiris: Bank Umum Syariah Indonesia) - Rawati, Mesis; Puteri, Hesi Eka (Jurnal Ilmiah Global Education, 2024)
Profitability is one of the factors influencing a company's value, and higher profitability accelerates the growth rate of assets in Sharia Commercial Banks in Indonesia. The objective of this study is to estimate the mediating effect through the Capital Adequacy Ratio variable, which represents the interaction pattern in explaining how Return on Assets (ROA) and Return on Equity (ROE) affect Price Book Value (PBV). This research utilizes Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis using WarpPLS 8.0. The study involved 12 respondents from Sharia Commercial Banks listed on the Indonesia Stock Exchange, selected through purposive sampling. The findings indicate a partial mediating effect of Capital Adequacy Ratio (CAR) in the relationship between ROA, ROE, and PBV. Based on the testing and discussion of the findings regarding the mediating effect of CAR in the relationship between ROA, ROE, and PBV in Sharia Commercial Banks in Indonesia, CAR partially mediates the relationship between ROA, ROE, and PBV as indicated by the Variance Accounted For (VAF). This relationship enriches the understanding that the positive effect of profitability on company value is mediated by the CAR process. The company's value is viewed through its ability to maintain CAR. Scientifically, this research contributes to the understanding of capital structure in business or banking, serving as a reference for companies and banks to enhance corporate value and profitability year after year by maintaining an optimal capital structure that avoids bankruptcy and strengthens capitalization.